Velar Closing Ratio As a Predictor for the Verlopharyngeal Function After Double Opposing Z-Plasty for Postpalatoplasty Velopharyngeal Insufficiency in Patients With Cleft Palate. (April 2021) - Wu, Cheng-Chun; Huang, Faye; Hsieh, Ching-Hua; Fu, Chih-Pin; Tsai, Yi-Lin; Lai, Jui-Pin
Background: This study was designed to identify the potential predictors of postoperative velopharyngeal function after double opposing Z-plasty (DOZP) for the treatment of velopharyngeal insufficiency (VPI) in patients who had prior palatoplasty for cleft palate. Methods: This retrospective study reviewed the medical records of consecutive patients who received DOZP for VPI after receiving a prior palatoplasty treating cleft palate between 2004 and 2017. The speech outcome of patient was measured using the Pittsburgh Weighted Speech Scale (PWSS) at 6 months following surgery and determined the outcome suggests velopharyngeal competence (PWSS ≤2) or incompetence (PWSS >2). Stepwise logistic regression was used to identify the variables for the prediction of competent surgical outcome. The specific receiver operating characteristic curves with an area under the curve (AUC) was used to evaluate the predictor related to the surgical outcome as competence. Results: The study included 93 patients. Age, relative velar length, velar lengthening, and closure pattern were not significantly associated with postoperative competence status of the patient. The only variable that predicted a successful surgical outcome was preoperative velar closing ratio. However, the accuracy of velar closing ratio in predicting a competent surgical outcome is only moderate (AUC = 70.37). Conclusion: The results of this study showed that preoperative velar closing ratio may predict, with moderate accuracy, a successful surgical outcome in patients with postpalatoplasty VPI who undergo DOZP. Therefore, in patients with a low preoperative velar closing ratio, some alternative surgical methods other than DOZP may be considered to avoid unsatisfactory surgical outcome.